315 Recent trends of road traffic fatalities in China: comparing national and subnational data sources. (1st September 2016) - Li, Qingfeng; He, Huan; Liang, Hailun; Bishai, David M; Hyder, Adnan A
Abstract : Background: This study aims to better understand public data sources and evaluate recent trends in road traffic fatalities (RTF) in China. Methods: We systematically reviewed and compared multiple national sources of RTF data. These included: population-based reports from the Ministry of Public Security (MPS), sample-based estimates from the vital registration system of Ministry of Health (MOH) and the Disease Surveillance Points System (DSP), as well as model-based estimates from the World Health Organisation (WHO) and the Global Burden of Disease Study (GBD). A comprehensive review of publications focused on subnational RTF was also conducted. We based our assessment of the recent trend of RTF on using fixed effects and random effects longitudinal models. Results: Despite the discrepancies in estimates, all national data sources indicated that RTF had been increasing prior to 2005. Since then, the MPS reports indicate a declining trend, DSP estimates showed a flat trajectory while estimates from MOH, GBD and WHO continue to show increases in RTF. Data from local death registration systems are largely consistent with MPS reports. Conclusions: Reflecting a non-representative sample, MOH data were used in generating model-based estimates by the WHO and GBD; consequently, the trends from these sources are open to. MPS and local independent jurisdictional health data indicate that RTF have been declining since 2005. This may be consistent with recent interventions to reduce RTF. China's experience may be of great value for other developing countries though RTF still impose a tremendous health burden in the country.